Chemically modified bitumens with enhanced rheology and adhesion properties to siliceous aggregates - Cuadri, A.A.; Partal, P.; Ahmad, N.; Grenfell, J.; Airey, G. (Elsevier, 2015)
Moisture damage is one of the major premature failures that worsens the performance and shortens service life of pavements. This research assesses the effect that two chemical modifiers (thiourea and an isocyanate-functionalized castor oil prepolymer) exerts on the bitumen rheology and on the resistance to potential moisture damage of asphalt mixtures based on siliceous aggregates. Both thiourea and the isocyanate-based prepolymer improve the viscous and viscoelastic behaviours of bitumen at high in-service temperatures, particularly the isocyanate-based reactive modifier. Likewise, the visual inspection of the degree of bitumen coating on loose mixtures exposed to water in a “rolling bottle” test, and further surface free energy measurements, showed that the bitumen modification by the isocyanate-based prepolymer seems to reduce moisture-induced damage on siliceous aggregates. Conversely, thiourea-based modification increases sensitivity of the bitumen–aggregate mixture to water. Different adhesion mechanisms, based on chemical or physical bonds with the aggregate surface, have been proposed for each modifier.